AI-Augmented Code Generation - erizo, juan jacob (PT. Lentera Ilmu Publisher, 2025)
AI-augmented code generation is transforming software development by enhancing productivity, reducing repetitive tasks, and improving code quality. Tools like GitHub Copilot, OpenAI Codex, and IntelliCode assist developers by providing real-time code suggestions, generating functions from natural language prompts, and detecting potential errors. This technology simplifies coding workflows, allowing programmers to focus on complex problem-solving rather than routine coding tasks.AI-powered tools rely on deep learning models trained on vast code repositories to understand context and generate relevant code snippets. While these tools significantly speed up development, they also introduce challenges such as security risks, computational costs, and the need for human oversight. Despite these concerns, AI-driven coding assistants are proving invaluable in modern software engineering, supporting applications in cloud computing, competitive programming, and full-stack development.Beyond simple code suggestions, AI assists with debugging, performance optimization, and even full project generation. As AI models continue to evolve, their integration into software development will further enhance efficiency and accessibility.